Pattern of pediatric dermatoses in a tertiary care centre of South West Rajasthan - Manisha Balai; Ashok Kumar Khare; Lalit Kumar Gupta; Asit Mittal; C M Kuldeep (Wolters Kluwer Medknow Publications, 2012)
Background: The evaluation for skin disorders forms an important component of primary health care practice for all including children. The prevalence of certain skin diseases in children can reflect status of health, hygiene, and personal cleanliness of a community. Aims: This study was planned to evaluate the magnitude of skin diseases, pattern of various dermatoses, factors contributing to these dermatoses and concurrent systemic disease among children up to five years of age. Materials and Methods: Consecutive 1000 children, aged up to five years, attending the Dermatology OPD of RNT Medical College and MB Government Hospital, Udaipur were the subjects of this study. A detailed general, systemic and cutaneous examination followed by relevant investigations were carried out. The findings were recorded in a proforma for analysis and interpretation of data. Results: One thousand twenty seven (1027) diagnoses were made in 1000 children. Etiological analysis revealed that majority (417; 40.60%) of dermatoses belonged to infection and infestation group followed by eczematous (358; 34.86%) and hypersensitivity (105; 10.22%) groups. Of the infection and infestation group, bacterial infection (141; 13.72%) was the most common entity followed by scabies (107; 10.42%), fungal (67; 6.52%), and viral infection (35; 3.40%). Conclusion: This study provides a preliminary baseline data for future clinical research. It might also help to assess the changing trends of pediatric dermatoses.